Centralized Control Center Implementation for Synergistic Operation of Distributed Multifunctional Single-Phase Grid-Tie Inverters in a Microgrid - Morales-Paredes, Helmo Kelis [UNESP]; Bonaldo, Jakson Paulo; Pomilio, Jose Antenor (Institute of Electrical and Electronics Engineers (IEEE), 2018)
This study discusses a centralized and coordinated control of distributed multifunctional inverters connected to an electric grid. The multifunctional operation is based on the conservative power theory, which makes it possible to identify undesired current components that can be compensated. The inverters that make up the microgrid are managed through a transmission control protocol/internet protocol (TCP/IP) communication network, allowing commands from a control center, while also allowing monitoring and gauging of electrical quantities of interest related to each of the inverters. Using the control center, it is possible to adjust the current necessary for compensation, which can be shared among inverters in a coordinated manner and according to their nominal capacities. Adjustments are made by sending references to certain indexes for desired power quality at the coupling point of each inverter. Experiment results explore some compensation alternatives, employing communication flexibility among the devices that comprise the microgrid.
Keywords: Conservative power theory (CPT); coordinated control; microgrids; multifunctional inverters; power quality (PQ)